Regioselective Metal‐Free C2−H Arylation of Quinoline N‐Oxides with Aryldiazonium Salts/Anilines under Ambient Conditions. Issue 8 (22nd June 2017) - Kumar, Rakesh; Kumar, Rakesh; Dhiman, Ankit Kumar; Sharma, Upendra
Abstract: Herein, a base‐promoted direct C2−H arylation of quinoline N ‐oxides with aryldiazonium salts under metal‐free conditions is reported. This reaction avoids the need for an oxidant, metal catalyst, or inert atmosphere and proceeds through a highly regioselective C−H bond functionalization to provide a series of C2‐arylated quinoline N ‐oxides. Abundantly available amines (anilines and heteroaryl amines) can also be employed as arylating agents through an in situ diazotization process, thereby affording a library of diverse 2‐arylquinoline N ‐oxides in moderate‐to‐good yields. The synthesized 2‐arylated quinoline N ‐oxides were further converted into C8‐substituted quinolines to demonstrate the applicability of this catalytic approach. A radical pathway is proposed for the C2 arylation, based on a preliminary mechanistic study. Abstract : I′ll C2 it : A base‐promoted direct C2−H arylation of quinoline N ‐oxides with aryldiazonium salts under metal‐free conditions has been developed that provides access to a series of C2‐arylated quinoline N ‐oxides.